SYNTACTIC EXPRESSION OF TOLERANCE IN UZBEK AND ENGLISH LITERATURE - Isroilova Ugiloy Isroil kizi (Modern American Journals, 2025)
This article explores the syntactic mechanisms used to express the concept of tolerance in Uzbek and English literary texts. It compares the structural patterns, sentence constructions, and grammatical strategies that convey moral and aesthetic values, focusing on how tolerance is linguistically encoded in both traditions. Through qualitative analysis of selected literary works, the study highlights how culture-specific narratives shape syntactic choices and influence the communicative style of authors. Findings show that while both languages use similar syntactic tools—such as modal constructions, passive voice, and concessive clauses—their frequency, positioning, and pragmatic load vary, reflecting differing cultural attitudes towards tolerance and moral ambiguity.
Keywords: syntax, tolerance, sentence structure, Uzbek literature, English literature, linguistic expression, comparative analysis, literary pragmatics